BINOL-based chiral aggregation-induced emission luminogens and their application in detecting copper(ii) ions in aqueous media. Issue 43 (14th October 2015) - Li, Nan; Feng, Honglian; Gong, Qian; Wu, Chunxiao; Zhou, Hao; Huang, Zhiyan; Yang, Jun; Chen, Xiaohua; Zhao, Na
Abstract : In this work, two chiral luminogens have been reported. They exhibit aggregation induced emission and annihilation of CD performance. Meanwhile, one of them can serve as a chiral fluorescent sensor for Cu 2+ . Abstract : Two novel chiral luminogens BINOM-CN and BINOP-CN derived from ( R )-1, 1′-binaphthol (BINOL) with aggregation-induced emission (AIE) characteristics were designed and synthesized. Dicyanomethylene and the substituent of the hydroxyl group have been found to be the key structural element for this unique AIE effect. Meanwhile, these two chiral AIE luminogens exhibit abnormal aggregation-induced annihilation of the circular dichroism (CD) signal, which is ascribed to the decrease of the dihedral angle between adjacent naphthalene rings in the aggregation state. With the assistance of the pyridine unit, BINOP-CN can serve as an excellent sensor for Cu 2+ . In the presence of Cu 2+, the fluorescence intensity and CD signals of BINOP-CN both decreased observably due to its ideal coordination with Cu 2+, which was further confirmed by X-ray crystallography. Moreover, the addition of Cu 2+ can induce the self-assembly of BINOP-CN.